Desempenho produtivo de bovinos zebuínos e cruzados em sistema de integração lavoura pecuária - Ângelo André Lampeão (2015)
Production performance evaluation was carried out for four genetic groups of zebu cattle and crossed in Crop and Livestock Integration System. For this porpose, 39 uncastrated male cattle were used thirteen 1/2 Aberdeen Angus x 1/2 Nelore (AN); eight 1/2 Charolês x 1/4 Aberdeen Angus x 1/4 Nelore (CAN); thirteen 1/2 Tabapuã x 1/4 Aberdeen Angus x 1/4 Nelore (TAN) e five 1/2 Tabapuã x 1/2 Nelore (TN), with age in avareg of 9 months and initial average weight of 167.92 kg; 183.16 kg; 135.58 kg and 131.50 kg for the AN group, CAN, TAN and TN respectively. For statistical analysis was used the SAS (2000) method and the comparison of the means was performed using the adjusted Tukey test, adopting a 5% significance level in a completely randomized. The animals remained under rotational grazing Panicum Maximum cv. Tanzânia with an average capacity rate of 3.88 AU / ha and herbage availability of 12.64%, with an average consumption of protein-energy-mineral supplement of 0.1% live weight (BW) in the dry season and 0.6% live weight (BW) in rainy season. were evaluated production and forage quality, dry matter intake (DMI), average daily gain (ADG) and feed efficiency (EA). The forage availability was 6440.22 kg DM / ha. No effects of genetic groups (P> 0.05) during the evaluation of the dry matter intake (DMI) of 7,45Kg / day, 7.37 kg / day, 6.63 kg / day and 6.10 kg / day CAN AN, TAN and TN respectively. In the dry season, there were differences (P <0.05) in ADG only between the AN group (0.419 kg) and TN (0.295 kg) in the other groups, was obtained 0.382 kg and 0.379 kg for TAN and CAN respectively. There were differences (P <0.05) between AN (0.797 kg) and CAN (0.636 kg) in the rainy season, and was observed in the other groups TAN (0.759 kg) and TN (0.770 kg). The genetic group Angus X Nellore was higher than the Tabapuã Nellore X group in the dry season due to greater retention of individual heterosis and high additive value. In the rainy season, Charolais X Angus X Nellore group has not adapted to the environmental conditions showed lower performance than the other groups. The dry matter intake and feed efficiency were similar in the different genetic groups in this study and may be indicated these genetic groups in crop and livestock integration systems in the recreates period.